The Impact of Domestic Violence on Family Harmony - Ardiyanti, Agnes Vania; Wardaningtyas, Lulu Khalilah; Faizah, Rayinda (Universitas Muhammadiyah Yogyakarta, 2023)
Domestic violence or what is often referred to as domestic violence does not only affect perpetrators and victims but also affects other family members. The purpose of this study is to obtain an overview of the impact of domestic violence on family harmony. The research method used is descriptive qualitative by interviewing two research subjects who have been directly exposed to domestic violence. The results of the study show that wives and children who experience domestic violence cause decreased harmony in the family. Family harmony can be seen from how communication, affection, mutual respect, cooperation, having time in the family, increasing spiritual well-being and minimizing conflict. A family is called harmonious if all family members feel happy which is marked by reduced tension, disappointment, and satisfaction with all of their circumstances and existence which includes the physical, mental, emotional and social aspects of all family members